Expression and potential role of FOSB in glioma - Qi, Min; Sun, Le-an; Zheng, Lan-rong; Zhang, Jia; Han, Yan-ling; Wu, Feng; Zhao, Jian; Niu, Wen-hao; Fei, Mao-xing; Jiang, Xiao-chun; Zhou, Meng-liang (Frontiers in Molecular Neuroscience, 2022)
Background FOSB is reported to be an oncogene in a variety of tumors. However, the expression and role of FOSB in glioma remain obscure. In this study, we aimed to explore the expression of FOSB in glioma and its biological role in glioblastoma multiforme (GBM). Methods Western blot, immunohistochemical staining, and quantitative real-time polymerase chain reaction (RT-qPCR) were used to detect the expression of FOSB in clinical samples. FOSB was knocked down in cells to determine the effects of FOSB on the phenotypic changes of tumors by plate cloning, CCK-8 assay, and Transwell assay. Finally, subcutaneous tumorigenesis in nude mice was used to observe the tumorigenesis of glioma cell lines after the knockdown of the FOSB gene. Results FOSB expression was higher in glioma compared with normal brain tissue. After the downregulation of FOSB, the expression of cleaved caspase-3 increased. Plate cloning and CCK-8 experiments showed that the proliferation of glioma cell lines decreased. The Transwell assay demonstrated that the glioblastoma cell lines had lower migration ability after the knockdown of FOSB. Finally, the tumor volume of U87 glioma cells in group sh-FOSB was smaller than that in the control group. The TUNEL staining in vitro showed that the apoptosis of sh-FOSB glioma cells increased. Conclusion FOSB was highly expressed in glioma tissues. The viability of glioma cells decreased, and the ability of glioma cells to proliferate and migrate was reduced when FOSB was downregulated. Hence, FOSB may promote the development and migration of gliomas.